HMGA2 regulation by miRNAs in cancer: Affecting cancer hallmarks and therapy response - Hashemi, Mehrdad; Rashidi, Mohsen; Hushmandi, Kiavash; ten Hagen, Timo L.M.; Salimimoghadam, Shokooh; Taheriazam, Afshin; Entezari, Maliheh; Falahati, Mojtaba (Pharmacological research, 2023)
High mobility group A 2 (HMGA2) is a protein that modulates the structure of chromatin in the nucleus. Importantly, aberrant expression of HMGA2 occurs during carcinogenesis, and this protein is an upstream mediator of cancer hallmarks including evasion of apoptosis, proliferation, invasion, metastasis, and therapy resistance. HMGA2 targets critical signaling pathways such as Wnt/β-catenin and mTOR in cancer cells. Therefore, suppression of HMGA2 function notably decreases cancer progression and improves outcome in patients. As HMGA2 is mainly oncogenic, targeting expression by non-coding RNAs (ncRNAs) is crucial to take into consideration since it affects HMGA2 function. MicroRNAs (miRNAs) belong to ncRNAs and are master regulators of vital cell processes, which affect all aspects of cancer hallmarks. Long ncRNAs (lncRNAs) and circular RNAs (circRNAs), other members of ncRNAs, are upstream mediators of miRNAs. The current review intends to discuss the importance of the miRNA/HMGA2 axis in modulation of various types of cancer, and mentions lncRNAs and circRNAs, which regulate this axis as upstream mediators. Finally, we discuss the effect of miRNAs and HMGA2 interactions on the response of cancer cells to therapy. Regarding the critical role of HMGA2 in regulation of critical signaling pathways in cancer cells, and considering the confirmed interaction between HMGA2 and one of the master regulators of cancer, miRNAs, targeting miRNA/HMGA2 axis in cancer therapy is promising and this could be the subject of future clinical trial experiments. [Display omitted]